PERMISSIVE PARENTING AND UNCONTROLLED SMARTPHONE USAGE HABITS IN PRESCHOOL CHILDREN: A QUALITATIVE CASE STUDY - Affriella, Siestie Ayu; Setiawan, M. Hery Yuli; Irmade, Oka (Jurnal Ilmiah Pendidikan Citra Bakti, 2026)
The increasing use of smartphones among preschool children has raised concerns regarding habit formation and behavioral development. This study aimed to analyze the role of permissive parenting in shaping uncontrolled smartphone usage habits in preschool children. This study employed a qualitative approach with a case study design conducted at Tunggur Kindergarten. The participants consisted of 5 parents and 5 children aged 5–6 years, supported by a teacher and a principal. Data were collected through semi-structured interviews, observations, and documentation, and analyzed using an interactive analysis model. The findings revealed that parents tended to provide smartphone access without consistent supervision or clear time limits. As a result, children developed repetitive usage habits characterized by high frequency, prolonged duration, and signs of dependency. Children also showed emotional responses such as crying and resistance when smartphone use was restricted. This study concludes that permissive parenting contributes significantly to the formation of uncontrolled smartphone usage habits. Active parental involvement is therefore essential to establish boundaries and ensure appropriate smartphone use in early childhood.